Identifying beliefs driving COVID-19 vaccination: Lessons for effective messaging - Sarah R. MacEwan; Eben Kenah; Graham N. Dixon; Jack Stevens; Leanna Perez Eiterman; Jonathan R. Powell; Christopher B. Gage; Laura J. Rush; Ashish R. Panchal; Ann Scheck McAlearney (Taylor & Francis Group, 2023)
ABSTRACTIncreasing vaccination acceptance has been essential during the COVID-19 pandemic and in preparation for future public health emergencies. This study aimed to identify messaging strategies to encourage vaccine uptake by measuring the drivers of COVID-19 vaccination among the general public. A survey to assess COVID-19 vaccination acceptance and hesitancy was advertised on Facebook in February-April 2022. The survey included items asking about COVID-19 vaccination status and participant demographics, and three scales assessing medical mistrust, perceived COVID-19 risk, and COVID-19 vaccine confidence (adapted from the Oxford COVID-19 vaccine confidence and complacency scale). The main outcome was vaccination, predicted by patient demographics and survey scale scores. Of 1,915 survey responses, 1,450 (75.7%) were included, with 1,048 (72.3%) respondents reporting they had been vaccinated. In a multivariable regression model, the COVID-19 vaccine confidence scale was the strongest predictor of vaccination, along with education level and perceived COVID-19 risk. Among the items on this scale, not all were equally important in predicting COVID-19 vaccination. The items that best predicted vaccination, at a given score on the COVID-19 vaccine confidence scale, included confidence that vaccine side effects are minimal, that the vaccine will work, that the vaccine will help the community, and that the vaccine provides freedom to move on with life. This study improved our understanding of perceptions most strongly associated with vaccine acceptance, allowing us to consider how to develop messages that may be particularly effective in encouraging vaccination among the general public for both the COVID-19 pandemic and future public health emergencies.